(3QSGdI ajeG NGda ajg bGdhf nhrQkTG ajeG Qhi Yf fGaYs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3gPG cJGHj CPcQ ajg Ef TGA Gddg JYGdi GdMQha GdJj NGda ajgG bGdhf hQTkG ajeG Qhi Yf fGaY s
(3BNQgG (B:s
(3hMPahgG (B[(3Cj jGA GdfOGA(B] (3aj bhdg JYGdi(B: (3jGYHGOj dGNha Ydjce Gdjhe h dG CfJe JMRfhf hHGddg GdJhajb JeJ HMeO Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(283 (3b(B) s
Keywords: (3GdbQGAGJ hGdJLhjOs